Czochralski growth and characterization of cerium doped calcium scandate. Issue 18 (26th April 2017) - Guguschev, C.; Philippen, J.; Kok, D. J.; Markurt, T.; Klimm, D.; Hinrichs, K.; Uecker, R.; Bertram, R.; Bickermann, M.
Abstract : A cylindrical cerium doped CaSc2 O4 bulk single crystal with a diameter of 20 mm and a total length of 70 mm was grown from the melt by the Czochralski method. Abstract : A cylindrical cerium doped CaSc2 O4 bulk single crystal with a diameter of 20 mm and a total length of 70 mm was grown from the melt by the Czochralski method. Due to competitive growth and grain selection, the crystal shows high crystalline quality, verified by X-ray diffraction (XRD) rocking curve measurements and by the energy dispersive Laue mapping (EDLM) method. Rocking curve measurements revealed full width at half maximum (FWHM) values of 24, 28 and 34 arcsec for 200, 020 and 002 reflexes, respectively. The anisotropic optical and thermal properties of the biaxial material were investigated by UV-vis spectroscopy, ellipsometry and by the laser flash technique along the main crystallographic orientations. TEM measurements confirmed that cerium is preferentially incorporated into the Ca-site.